2010
DOI: 10.1021/ol102550c
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescent Signaling of Oxone by Desulfurization of Thioamide

Abstract: The chemosignaling of the oxidant Oxone by selective desulfurization of a thioamide was investigated. Pyrene-thioamide was efficiently converted to its amide analogue by reaction with Oxone, resulting in a pronounced fluorescent turn-on type signaling. Selective signaling of Oxone in aqueous solution was possible in the presence of representative alkali and alkaline earth metal ions, as well as common anions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…14,15,36,37 Furthermore, the reaction of Oxone® with N,N-diethyl-1-pyrene-carboxamide was applied for uorescence sensing of this oxidant. 24 We found that Oxone® reacts smoothly with thioamides 1a-j in acetonitrile-water at room temperature to afford the corresponding amides 2a-j in high yields (86-100%, Scheme 1).…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…14,15,36,37 Furthermore, the reaction of Oxone® with N,N-diethyl-1-pyrene-carboxamide was applied for uorescence sensing of this oxidant. 24 We found that Oxone® reacts smoothly with thioamides 1a-j in acetonitrile-water at room temperature to afford the corresponding amides 2a-j in high yields (86-100%, Scheme 1).…”
Section: Resultsmentioning
confidence: 92%
“…12,[14][15][16] Moreover, these compounds were used in the synthesis of polymers with tunable luminescent properties 17 and in the labelling of nucleosides. 7,8,[18][19][20][21][22] In contrast to amides, pyrene-1-carbothioamides are only weakly uorescent 23,24 because of the internal quenching effect of the thiocarbonyl group. Since some chemical species desulfurize thioamides (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We added oxalyl chloride to a mixture of pyrene-1-carboxylic acid and 1-naphthoic acid in methylene chloride and added dimethyl formamide after approximately 1–2 drops [ 23 ] ( Scheme S1 ). The mixture was stirred at room temperature to maintain the reaction for approximately 4 h. Once the reaction was completed, the methylene chloride was evaporated, and 1 h of vacuum was performed.…”
Section: Methodsmentioning
confidence: 99%
“…Coumarin, as well as other related fluorescent carbonyl‐containing systems, exhibit red‐shifted emissions and decreased quantum yields upon thionation with LR. Additionally, in many cases the thio form can be converted back to the respective oxo form through various means, a transformation which often shows a turn‐on fluorescence response [5,7–9] . Similarly, non‐aromatic aminophosphonic esters have been converted to their respective thio forms as well [10–12] .…”
Section: Figurementioning
confidence: 99%